Coix Seed-Based Milk Fermented With Limosilactobacillus reuteri Improves Lipid Metabolism and Gut Microbiota in Mice Fed With a High-Fat Diet - Zhoujie Yang; Xiaoli Zhu; Anyan Wen; Jingqi Ran; Likang Qin; Yi Zhu (Frontiers in Nutrition, 2022)
The aim of this study was to investigate the effects of coix seed-based milk (CSM) fermented with Limosilactobacillus reuteri (L. reuteri) on dyslipidemia and the composition of the intestinal microbiota in high fat diet (HFD)-fed mice. Changes in the body weight, serum lipid levels, activities of hepatic oxidative stress factors, expression of lipid-related genes, and composition of the intestinal microbiota of HFD-fed mice after supplementation with CSM were determined. The results showed that intake of CSM reduced the body weight gain as well as serum total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) levels, and increased the high-density lipoprotein cholesterol (HDL-C) levels in the mice. Meanwhile, supplementation with CSM could relieve liver oxidative stress, down-regulate the expression of genes related to lipid synthesis, and prevent liver fat accumulation in mice fed with HFD. The 16S rRNA sequencing of the intestinal microbiota showed that CSM regulated the gut microbiota community structure at different taxonomic levels, and reversed gut dysbiosis induced by HFD. The relative abundance of Muribaculaceae, Lachnospiraceae, Dubosiella and Akkermansia which are negatively correlated with blood lipid levels were significantly increased by the intervention of CSM, while the relative abundance of Desulfovibrionaceae, Ruminococca-ceae_UCG-014, Psychrobacter, and Staphylococcus which have positive correlation with blood lipid levels were significantly decreased. These results indicated that CSM might serve as a novel and promising dietary supplement for ameliorating hyperlipidemia and intestinal microbiota disorders caused by HFDs.